2021
DOI: 10.3389/fmicb.2020.588884
|View full text |Cite
|
Sign up to set email alerts
|

Self-Adaptation of Pseudomonas fluorescens Biofilms to Hydrodynamic Stress

Abstract: In some conditions, bacteria self-organize into biofilms, supracellular structures made of a self-produced embedding matrix, mainly composed of polysaccharides, DNA, proteins, and lipids. It is known that bacteria change their colony/matrix ratio in the presence of external stimuli such as hydrodynamic stress. However, little is still known about the molecular mechanisms driving this self-adaptation. In this work, we monitor structural features of Pseudomonas fluorescens biofilms grown with and without hydrody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Note that the cell-to-cell interaction we used is effective in the sense that it includes contributions from cell-VPS and VPS-VPS interactions; recent work has shown that these more complicated interactions can be modeled efficiently using an effective intercellular potential. [9,49] 27 cells in total are randomly distributed and relaxed in a simulation box of 10 × 10 × 10 µm 3 before performing the sheared flow simulation. As shown in Figure 3a, starting from a random organization (at 0 s −1 ), upon increasing the shear rate the simulated biofilm structure first becomes denser, and cells in the aggregate tend to align along the shear direction (at 60 s −1 ).…”
Section: Nonequilibrium Molecular Dynamics (Nemd) Simulationsmentioning
confidence: 99%
“…Note that the cell-to-cell interaction we used is effective in the sense that it includes contributions from cell-VPS and VPS-VPS interactions; recent work has shown that these more complicated interactions can be modeled efficiently using an effective intercellular potential. [9,49] 27 cells in total are randomly distributed and relaxed in a simulation box of 10 × 10 × 10 µm 3 before performing the sheared flow simulation. As shown in Figure 3a, starting from a random organization (at 0 s −1 ), upon increasing the shear rate the simulated biofilm structure first becomes denser, and cells in the aggregate tend to align along the shear direction (at 60 s −1 ).…”
Section: Nonequilibrium Molecular Dynamics (Nemd) Simulationsmentioning
confidence: 99%
“…Therefore, as an increase in solid content not necessarily leads to an increase in mechanical strength, we hypothesize that only some biofilm components contribute to the network strength and elasticity. Recent work found that P. fluorescens exposed to hydrodynamic stresses formed mechanically stronger biofilms compared to those formed in static conditions, and this was attributed specifically to an increase in EPS content [65]. This increase in matrix components was hypothesized to lead to an increase in cross-linking density in the biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that genes that play a regulatory role in gluconeogenesis are significantly upregulated in biofilm cells compared with free cells [ 37 , p. 139]. It is reported that carbohydrates are the major composition of biofilms [ 38 ]. Carbon sources play a necessary role in the survival, growth, and infection of strains [ 39 , pp.…”
Section: Discussionmentioning
confidence: 99%